1997
DOI: 10.1007/pl00005114
|View full text |Cite
|
Sign up to set email alerts
|

A re-appraisal of the nature of the atropine-resistant contraction to electrical field stimulation in the human isolated detrusor muscle

Abstract: We investigated whether in human isolated detrusor strips the atropine-resistant contractile response to electrical field stimulation was mediated by ATP (or a related purine), as previously shown in the urinary bladder of other mammalian species. Electrical stimulation (1-50 Hz for 5 s at 1 min intervals, 0.1 ms pulse width, 60 V) elicited reproducible, frequency-dependent twitch contractions, which were markedly reduced by atropine (10 microM). Tetrodotoxin (TTX: 1 microM) inhibited contractile responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The presence of an atropine-resistant nerve component in the human bladder has been controversial, although most authors did find a small component, usually less than 5 % in healthy bladder [31,50,166,262,296,371,446,462,518,583,611,620,631,652]. One early report suggested that the NANC component in the human female bladder was greater than in the male bladder, amounting to about 50 % of the nervemediated contractile response of the bladder [163].…”
Section: Healthy Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an atropine-resistant nerve component in the human bladder has been controversial, although most authors did find a small component, usually less than 5 % in healthy bladder [31,50,166,262,296,371,446,462,518,583,611,620,631,652]. One early report suggested that the NANC component in the human female bladder was greater than in the male bladder, amounting to about 50 % of the nervemediated contractile response of the bladder [163].…”
Section: Healthy Bladdermentioning
confidence: 99%
“…One paper claimed that the atropine-resistant component of excitatory transmission in the human bladder was not mediated by neural release of ATP in spite of the presence of P2 receptors in the effector cells [652].…”
Section: Healthy Bladdermentioning
confidence: 99%
“…This may be taken as indirect evidence of changes in the cholinergic functions of the bladder, since normally the atropine-resistant component is almost negligible (Andersson, 1993;Tagliani et al, 1997;. Alternatively, there may also be an up-regulation of the nonadrenergic, noncholinergic (NANC) component of contraction (see Section III.A.7.).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…Sibley (1984) verified the occurrence of atropine resistance in hypertrophic bladder muscle, but also showed that the atropine-resistant response was resistant to TTX, suggesting that it was not nerve mediated, but that it was caused by direct muscle stimulation. Tagliani et al (1997) concluded, based on their results, that the atropine-resistant component may reflect direct smooth muscle excitation, since the human detrusor has a very short chronaxie. In contrast, Smith and Chapple (1994) showed that the NANC response from overactive, obstructed bladders was eliminated by TTX.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…ATP has been determined as a parasympathetic cotransmitter in numerous species (11) as well as a primary activator of afferent sensory nerves during bladder distension (4,14). Interestingly, while the purinergic component of neurally evoked contractions in normal human bladder is almost negligible (4,32), the role of ATP in the human bladder enhances significantly with aging (35) and in pathological conditions including neurogenic bladder, outflow obstruction, idiopathic detrusor instability, and interstitial cystitis (2,23,28,29), suggesting that endogenous nucleotides may have special roles in bladder dysfunctions.…”
mentioning
confidence: 99%